Genetic and phenotypic time trends of litter size, piglet mortality, and birth weight in pigs - Knap, Pieter W.; Knol, Egbert F.; Sørensen, A. Christian; Huisman, Abe E.; van der Spek, Dianne; Zak, Louisa J.; Granados Chapatte, Ana; Lewis, Craig R. G. (Frontiers in Animal Science, 2023)
Introduction Litter size in pigs has increased steadily since 1990. Because of unfavorable genetic correlations with piglet mortality, breeding goals should include survival traits next to litter size. Unbalanced breeding programs that neglect this requirement have produced increased mortality levels, attracting negative public attention. Balanced breeding does not have this disadvantage, but the general public is largely unaware of this. Methods We present long-term time trends as realized in commercial breeding. The data includes (i) phenotypes of litter size, piglet birth weight, and piglet mortality, as used in routine breeding value estimation; and (ii) the genomic Best Linear Unbiased Prediction (gBLUP) estimated breeding values thus obtained. Piglet mortality (2001–2022) and birth weight (2009–2022) phenotypes were related to litter size by recording year. Estimated breeding values (EBVs) for the mortality traits were regressed on those for litter size by birth year (2012–2022). Results Average litter size is very weakly correlated to the mortality (R2 ≤ 0.06) and birth weight (0.07 ≤ R2 ≤ 0.26) traits, and those correlations are unfavorable (antagonistic) within each year. However, all traits analyzed here show favorable simultaneous phenotypic and genetic trends over time: the antagonisms are neutralized by balanced breeding. Above the annual mean litter size level, farrowing and lactation mortality rates increased with increasing litter size in every year (unfavorable), but the annual intercepts and the slopes decreased from 2001 to 2022 (favorable). Average litter birth weight decreased with litter size in every year (unfavorable), but the annual intercepts increased and the slopes decreased from 2009 to 2022 (favorable). The within-litter birth weight variation coefficient increased with litter size in every year (unfavorable), but the annual intercepts decreased from 2009 to 2022 (favorable). The proportion of low birth weights (i.e.,< 0.9 kg) for a given litter size is decreasing over time, and the critical birth weight level (below which lactation mortality increases strongly) is clearly population dependent and changes over time too. Discussion The increases in litter size and piglet survival rates due to balanced breeding policies lead to reduced total numbers of dead piglets (i.e., per country, per year) coinciding with a certain pig production volume (i.e., with a certain total number of weaned piglets).